La Webquest para el desarrollo del aprendizaje significativo en el área de Ciencias Naturales en los niños de Séptimo año de educación básica de la Unidad Educativa “Nuestra Señora de Fátima periodo 2018-2019 - Rojas Broncano, Maritza Catherine (2021)
The title of this research is "THE WEBQUEST FOR SIGNIFICANT LEARNING’S DEVELOPMENT, IN NATURAL SCIENCES’ AREA, FOR CHILDREN OF SEVENTH YEAR OF BASIC EDUCATION IN UNIDAD EDUCATIVA "NUESTRA SEÑORA DE FÁTIMA" IN THE CHIMBORAZO PROVINCE, SCHOOL YEAR 2018-2019. Its objective is to apply Information and Communication Technologies specifically the Webquest methodology as a didactic proposal, to achieve meaningful and functional learning in students. This research had a qualitative approach because purpose was to discover how the Webquest can be used in the treatment of information and digital competence. The data was collected directly at the site of the research events, during the first quarter of the 2018-2019 school year, Descriptive; because the usefulness of ICTs in the classroom was described, Bibliographic; because information was collected in different sources. The research was carried out with a population of twenty-two students, applying the technique of observation and survey, each one with its respective instrument. For the analysis of the results, the respective measurement units and procedural methods were taken in consideration, thanks to the interpretation of data through a narrative analysis of discourse and statistical tables of the evaluation. With these results the research process is finalized and the conclusion is that the Webquest can be applied in classrooms as a methodological strategy that helps to facilitate the teaching-learning process, allowing students to develop cognitive and digital skills.